Ethics for our times - "Nadkarni, M.V" (New Delhi, 2011)
This book analyses the relevance of Gandhian thought in negotiating with contemporary dilemmas. Critically probing into conventional notions of 'good' and 'bad', it presents a comprehensive analysis of ethics as a conceptual framework and guide to the problems of rapidly globalizing societies. Nadkarni explores issues related to economic development, environment, humanism, and religion in the context of modern ethical inquiries like social justice, equity, and harmony across different sections in societies. He stresses the need for a holistic approach to resolve moral questions in everyday life. Balancing Western notions of the ethical and the Hindu notions of Dharma, the author analyses Gandhi, the thinker, activist, and philosopher. He presents an engaging connection between three systems of thought-ethics, Gandhian principles, and the Hindu scriptures.
Keywords: Gandhian thought and principles